In vivo personalized finite element modeling of the knee joint derived from MRI images: Methodology applied on one contact problem including bones, cartilages and menisci - Sangeux, Morgan; Marin, Frédéric; Charleux, Fabrice; Ho Ba Tho, Marie-Christine (European Journal of Computational Mechanics, 2009)
This paper adresses the methodology used to model the knee joint in vivo from MRI images. The knee joint model obtained is subject specific. The paper presents all the treatment procedure: Geometrical acquisitions, Joint movement analysis, Meshing techniques and nonlinear finite element modeling with contact between the bones, the cartilage and the menisci. The model provides the contact pressure applied on the various components of the joint for one normal subject.